2017
DOI: 10.3347/kjp.2017.55.1.65
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Taenia asiatica Infection Diagnosed by Colonoscopy

Abstract: A case of Taenia asiatica infection detected by small bowel series and colonoscopy is described. The patient was a 42-year-old Korean man accompanied by discharge of movable proglottids via anus. He used to eat raw pig liver but seldom ate beef. Small bowel series radiologic examinations showed flat tape-like filling defects on the ileum. By colonoscopy, a moving flat tapeworm was observed from the terminal ileum to the ascending colon. The tapeworm was identified as T. asiatica by mitochondrial DNA sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Meat inspection of 6 seropositive pigs (6 infected) [ 39 ] na na + [ 21 ] Japan + [ 22 ] Laos Meat inspection of 590 pigs (5 infected) [ 10 ]. OIE reported cases occurring during 2005–2017 na na Meat inspection of 590 pigs (1 infected) [ 10 ] na Malaysia Mongolia OIE reported cases occurring during 2005–2017 na na Myanmar Meat inspection of 300 pigs (71 infected) [ 40 ] na na North Korea + [ 27 ] Philippines + [ 28 ] Singapore South Korea + [ 32 ] Thailand + [ 33 ] + [ 33 ] + [ 33 ] Vietnam Tongue examination of 172,087 pigs (109 infected) [ 41 ]. OIE reported cases occurring during 2005–2017 na na + [ 12 ] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meat inspection of 6 seropositive pigs (6 infected) [ 39 ] na na + [ 21 ] Japan + [ 22 ] Laos Meat inspection of 590 pigs (5 infected) [ 10 ]. OIE reported cases occurring during 2005–2017 na na Meat inspection of 590 pigs (1 infected) [ 10 ] na Malaysia Mongolia OIE reported cases occurring during 2005–2017 na na Myanmar Meat inspection of 300 pigs (71 infected) [ 40 ] na na North Korea + [ 27 ] Philippines + [ 28 ] Singapore South Korea + [ 32 ] Thailand + [ 33 ] + [ 33 ] + [ 33 ] Vietnam Tongue examination of 172,087 pigs (109 infected) [ 41 ]. OIE reported cases occurring during 2005–2017 na na + [ 12 ] …”
Section: Resultsmentioning
confidence: 99%
“…Cysticercosis is not considered endemic in South Korea [ 31 ]. However, a recent case report of T. asiatica taeniosis showed that sporadic transmission is still suspected within South Korea [ 32 ]. Epidemiological surveys of pigs in rural areas are needed to confirm or refute the presence of porcine cysticercosis in South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Human taeniases are caused by the tapeworm species of Taenia solium , Taenia asiatica , or Taenia saginata . Among them, T. asiatica is mainly distributed in Asian countries, and is the dominant tapeworm species in South Korea [ 1 , 2 ]. Due to morphological similarity, T. asiatica has been confused with T. saginata , even by experienced parasitologists.…”
mentioning
confidence: 99%
“…Korean T. saginata has been more frequently observed among people with a dietary history of ingesting raw pork than raw beef. This is interesting in that the intermediate host of T. saginata is not the pig, but the cattle [ 2 , 3 ]. This issue was finally solved when South Korean taeniases originally diagnosed as T. saginata were revealed to be actually T. asiatica , which shares a common intermediate host (the pig) with T. solium [ 3 ].…”
mentioning
confidence: 99%
“…Recently, diphyllobothriosis is reemerging because of expanded global importation and increased popularity of eating raw fish [1] . There are some imaging modalities for diagnosis of tapeworms such as small bowel series [2] , capsule endoscopy [3] , [4] , [5] , and ultrasonography (US). In this paper, we present a case whose diphyllobothriasis could be diagnosed with characteristic US findings that have not previously been reported.…”
Section: Introductionmentioning
confidence: 99%